Leucine zipper and ICAT domain containing (LZIC) protein regulates cell cycle transitions in response to ionizing radiation. Issue 9 (3rd May 2019) - Skalka, George; Hall, Holly; Somers, Joanna; Bushell, Martin; Willis, Anne; Malewicz, Michal
ABSTRACT: Common hallmarks of cancer include the dysregulation of cell cycle progression and the acquisition of genome instability. In tumors, G1 cell cycle checkpoint induction is often lost. This increases the reliance on a functional G2/M checkpoint to prevent progression through mitosis with damaged DNA, avoiding the introduction of potentially aberrant genetic alterations. Treatment of tumors with ionizing radiation (IR) utilizes this dependence on the G2/M checkpoint. Therefore, identification of factors which regulate this process could yield important biomarkers for refining this widely used cancer therapy. Leucine zipper and ICAT domain containing (LZIC) downregulation has been associated with the development of IR-induced tumors. However, despite LZIC being highly conserved, it has no known molecular function. We demonstrate that LZIC knockout (KO) cell lines show a dysregulated G2/M cell cycle checkpoint following IR treatment. In addition, we show that LZIC deficient cells competently activate the G1 and early G2/M checkpoint but fail to maintain the late G2/M checkpoint after IR exposure. Specifically, this defect was found to occur downstream of PIKK signaling. The LZIC KO cells demonstrated severe aneuploidy indicative of genomic instability. In addition, analysis of data from cancer patient databases uncovered a strong correlation between LZIC expression and poor prognosis in several cancers. Our findings suggest that LZIC is functionally involved in cellular response to IR, and its expression level could serve as a biomarker for patient stratification in clinical cancer practice.